Role of genetic variants and DNA methylation of lipid metabolism-related genes in metabolic dysfunction-associated steatotic liver disease - Wang, Jun-Jie; Chen, Xiao-Yuan; Zhang, Yi-Rong; Shen, Yan; Zhu, Meng-Lin; Zhang, Jun; Zhang, Jun-Jie (Frontiers in Physiology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD), is one of the most common chronic liver diseases, which encompasses a spectrum of diseases, from metabolic dysfunction-associated steatotic liver (MASL) to metabolic dysfunction-associated steatohepatitis (MASH), and may ultimately progress to MASH-related cirrhosis and hepatocellular carcinoma (HCC). MASLD is a complex disease that is influenced by genetic and environmental factors. Dysregulation of hepatic lipid metabolism plays a crucial role in the development and progression of MASLD. Therefore, the focus of this review is to discuss the links between the genetic variants and DNA methylation of lipid metabolism-related genes and MASLD pathogenesis. We first summarize the interplay between MASLD and the disturbance of hepatic lipid metabolism. Next, we focus on reviewing the role of hepatic lipid related gene loci in the onset and progression of MASLD. We summarize the existing literature around the single nucleotide polymorphisms (SNPs) associated with MASLD identified by genome-wide association studies (GWAS) and candidate gene analyses. Moreover, based on recent evidence from human and animal studies, we further discussed the regulatory function and associated mechanisms of changes in DNA methylation levels in the occurrence and progression of MASLD, with a particular emphasis on its regulatory role of lipid metabolism-related genes in MASLD and MASH. Furthermore, we review the alterations of hepatic DNA and blood DNA methylation levels associated with lipid metabolism-related genes in MASLD and MASH patients. Finally, we introduce potential value of the genetic variants and DNA methylation profiles of lipid metabolism-related genes in developing novel prognostic biomarkers and therapeutic targets for MASLD, intending to provide references for the future studies of MASLD.